Students' Perception in Learning Speaking through Charades Game - Wida Ayuwandini; Yousef Bani Ahmad; Totoh Tauhidin Abas (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
Learning English speaking is well-known and taught as a foreign language in school. Among four significant skills, speaking is part of the essential skill because its role fundamentally serves as a means of communication. However, there are problems found in the class such as learners’ lack of self-confidence and lack of English vocabulary. This study is focused on students’ perception of the use Charades game in learning English speaking. The participant of this study is five students from junior high school in Karawang. Interview is the instruments use to conduct information related to the learners’ perception of learning English speaking through the Charades game. The data was analyzed through Miles and Huberman's steps. The result of the findings and discussion of data showed that all participants who participated in this study did show a positive perception of charades game and it seems that charades game makes a positive environment during learning English speaking thus the students feel enjoyed and fun when play it. Key words: Charades Game, Learning Speaking, Perception